First-order-like transition in salt-induced macroion-polyelectrolyte desorption - de Carvalho, S. J. [UNESP] (Epl Association, European Physical Society, 2010)
The salt effect on the adsorption-desorption transition of polyelectrolyte chains onto oppositely charged spherical macroions is investigated by means of the Metropolis Monte Carlo simulations and the weighted histogram analysis method. Verifying the variation of the mean binding energy and of the radius of gyration with the increase of the ionic strength it was possible to identify the coexistence between adsorbed and desorbed states. According to the free-energy profile as a function of the radius of gyration (order parameter) it was evidenced that the transitions are discontinuous and that the macroion charge dependence of the critical ionic strength is in agreement with the experimental data. Copyright (C) EPLA, 2010